2012
DOI: 10.1021/am2014162
|View full text |Cite
|
Sign up to set email alerts
|

MWCNTs/P(St-co-GMA) Composite Nanofibers of Engineered Interface Chemistry for Epoxy Matrix Nanocomposites

Abstract: Strengthened nanofiber-reinforced epoxy matrix composites are demonstrated by engineering composite electrospun fibers of multi-walled carbon nanotubes (MWCNTs) and reactive P(St-co-GMA). MWCNTs are incorporated into surfacemodified, reactive P(St-co-GMA) nanofibers by electrospinning; functionalization of these MWCNT/P(St-co-GMA) composite nanofibers with epoxide moieties facilitates bonding at the interface of the cross-linked fibers and the epoxy matrix, effectively reinforcing and toughening the epoxy resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 42 publications
5
49
0
Order By: Relevance
“…However, the effect of CNTs or other nanofillers on crosslinking has been less studied. Our experimental studies 64 and observations have shown that incorporation of CNTs considerably decreases crosslinking density in epoxy. This effect may be seen by monitoring the reduced glass transition temperature of composites (Tg) 64 or by directly determining crosslinking density by the Soxhlet extraction technique.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…However, the effect of CNTs or other nanofillers on crosslinking has been less studied. Our experimental studies 64 and observations have shown that incorporation of CNTs considerably decreases crosslinking density in epoxy. This effect may be seen by monitoring the reduced glass transition temperature of composites (Tg) 64 or by directly determining crosslinking density by the Soxhlet extraction technique.…”
mentioning
confidence: 52%
“…Our experimental studies 64 and observations have shown that incorporation of CNTs considerably decreases crosslinking density in epoxy. This effect may be seen by monitoring the reduced glass transition temperature of composites (Tg) 64 or by directly determining crosslinking density by the Soxhlet extraction technique. The lack of attractive interactions 10 at the interface can lead to depression of Tg relative to bulk values 65 .…”
mentioning
confidence: 52%
“…17,[43][44][45] If the solution is at a semi-dilute unentangled concentration regime, this jet disintegrates into micron sized droplets. The formation of super hydrophobic surfaces is possible once these droplets of a hydrophobic polymer dry out on a film.…”
Section: Formation Of Dual Scale Roughness Via Competing Solventsmentioning
confidence: 99%
“…In literature, several polymer matrices are reported for CNTs reinforced with nanofiber/fibers that benefit from CNTs-polymer attractive interactions [35][36][37]. For instance, recent experimental observations indicated that P(St-co-GMA) containing aromatic rings have attractive π-π interaction with the graphitic side walls of CNTs [38],which is called "π -stacking". This interaction leads to CNTs bundles which are major obstacles to their processing [39].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers containing aromatic rings are able to wrap CNTs via π-π stacking and van der Waals interactions between the polymer chain and nanotube surface [51]. Ozden-Yenigun et al used surface reactive copolymer (P(St-co-GMA)) and successfully produced CNTs reinforced electrospun nanofibers without any modification, they reported the enhancement in flexural strength (15%) and flexural modulus (20%) within the incorporation of CNTs into epoxy resin [38]. Charitidis et al used PVB as matrix in CNTs integrated nanocomposites to enhance electrical and thermal properties [52,53].…”
Section: Introductionmentioning
confidence: 99%